Lifting the mantle of protection from Weber's presuppositions in his theory of bureaucracy - Button, Graham; Martin, David; O'Neill, Jacki; Colombino, Tommaso (Human Studies, 2012)
It has been previously remarked upon (Sharrock and Button, 2007) that ethnomethodology is accused by whatever hue of a formal sociology concerned with primordial social structural matters such as ‘power’, ‘authority’, ‘bureaucracy’, ‘the state’, and the like, that it does not, cannot, deal with them. It has also been remarked upon (Sharrock and Button, 2007) that this is not a true characterisation of ethnomethodology which is as interested in these everyday matters of as it is in any everyday matter. It is just that it does not attach to them any primacy in the description of social affairs. Rather, ethnomethodology’s interest in them is conditioned by their appearance within the everyday affairs of members, in practical courses of action and interaction – how they are oriented to, and thereby made relevant for, and in, actual occasions of action and interaction.